The bank lending and balance sheet channels of monetary policy: a theoretical analysis - Gumede, Nomdumiso Beryl (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2013)
The credit channel and its significance in the monetary policy transmission mechanism has been a point of contention among policy makers and economists for many years. In the early stages of this debate the monetarist view shaped thinking on the topic and cultivated the belief that the money supply is exogenously determined and that commercial banks playa minor role in the monetary transmission process. However, over the years, the credit view presented by Bernanke and Blinder (1988) has gained momentum. In contrast to the monetarist view, the credit view abandons the assumption of perfect substitutability and argues that due to their credit provision activities, financial institutions playa significant role in the transmission of monetary policy. The credit channel consists of two sub channels, the bank lending and balance sheet channels. In both, deposits drive loans and changes in monetary policy are effected through interest rates and their impact on borrowers' balance sheets, bank reserves, bank deposits and ultimately the quantity of bank loans supplied. Disyatat (2010) re-examines the conventional view and presents an argument against the foundation upon which the theories are based. Using this as a basis, and motivated by the vast amount of empirical literature that already exists on this topic, both in South Africa and abroad, this research provides a theoretical analysis of the credit channel and its relative importance in the monetary policy transmission mechanism. The exogenous/endogenous nature of money supply is considered and its implications for the existence and operation of the credit channel set out. It is found that, in order for a credit channel to operate efficiently in an economy, money supply should be endogenously determined. Moreover, a theoretical argument supporting Disyatat's (2010) revised credit channel is presented; it is concluded that, with a slight variation to Disyatat's proposed model, a single, unified channel exists.
Keywords: Monetary policy; Money; Bank loans; Financial sheets